Massive rare desmoplastic fibroma of the ilium and ischium in a young adult: A case report. Issue 48 (December 2017) - Ma, Xin-Nan; Qiang, Shuai; Liu, Tian-Yi; Cao, Mei-Yu; Lv, Song-Cen
Abstract: Rationale: Desmoplastic fibroma (DF) is a rare, locally invasive but benign bone tumor. It represents one of the rarest bone diseases, with an incidence of only 0.11% of all primary bone tumors. Patient concerns: Herein, a case of massive and unusual DF, with simultaneous involvement of ilium and ischium, is described. A 29-year-old man suffered minor pain in his right hip for 2 years. It worsened after sudden movements, which prevented him from walking normally. Physical examination showed a limitation when the right hip was flexed and a percussion pain on the hip region. A medical imaging examination showed that the right ilium and ischium had a massive bone lesion. The top of acetabular had very little bone left and a fracture was likely at any time. No prominent body weight loss was noted, because there was no extensive invasion to the adjacent soft tissue. Diagnoses: DF of the Ilium and Ischium. Interventions: The patient underwent a surgery involving curettage and grafting to maintain the stability of the pelvis. Outcomes: The definitive pathological diagnosis was DF, without evidence of malignancy. The postoperative recovery course at 3-month follow-up was uneventful. Lessons: To the authors' knowledge, such a massive DF involving both ilium and ischium has been rarely reported. Young patients require appropriate and timely treatment modalities.